Logística de Almacenamiento Como Factor de Desarrollo Competitivo de la Empresa Amazon Durante el periodo 2008 – 2018 (2019)
The electronic commerce or e-commerce advances at a fleeting speed, with constant increases both in the number of daily transactions that are made by this means, as in volumes of income; becoming a current phenomenon of great importance and increasingly replacing traditional commerce. Amazon is an American e-commerce company, which took its first steps with the commercialization of books through the internet and it took very little time to achieve success; It is currently considered the most valuable brand in the world. This paper analyzes the role of storage logistics within the development and competitiveness that the electronic giant has acquired during the period 2008 - 2018, since one of the determining factors of this exponential growth has been its warehouse management, because it has developed services such as fast deliveries to satisfy its customers, and therefore has logistics centers that handle orders; In these centers, not only the goods are stored, but they are also distribution centers in which employees select, package and ship orders quickly and efficiently.